1999
DOI: 10.1182/blood.v93.8.2502
|View full text |Cite
|
Sign up to set email alerts
|

HFE Mutations Analysis in 711 Hemochromatosis Probands: Evidence for S65C Implication in Mild Form of Hemochromatosis

Abstract: Hereditary hemochromatosis (HH) is a common autosomal recessive genetic disorder of iron metabolism. The HFE candidate gene encoding an HLA class I-like protein involved in HH was identified in 1996. Two missense mutations have been described: C282Y, accounting for 80% to 90% of HH chromosomes, and H63D, which is associated with a milder form of the disease representing 40% to 70% of non-C282Y HH chromosomes. We report here on the analysis of C282Y, H63D, and the 193A→T substitution leading to the S65C missens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
2
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(115 citation statements)
references
References 20 publications
8
96
2
9
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood leucocytes and analysed both for the three main HFE mutations (C282Y, H63D, S65C) and for the main transferrin receptor polymorphism using polymerase chain reaction (PCR) and restriction analysis of the amplified fragment as previously described. 20,34,36 The frequencies of the alleles and genotypes were compared with the results obtained from a previous survey conducted in the general population from the same geographical area for HFE 18 or with data reported in the general population in a previous large-scale study by other authors. 34…”
Section: Genetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from peripheral blood leucocytes and analysed both for the three main HFE mutations (C282Y, H63D, S65C) and for the main transferrin receptor polymorphism using polymerase chain reaction (PCR) and restriction analysis of the amplified fragment as previously described. 20,34,36 The frequencies of the alleles and genotypes were compared with the results obtained from a previous survey conducted in the general population from the same geographical area for HFE 18 or with data reported in the general population in a previous large-scale study by other authors. 34…”
Section: Genetic Analysismentioning
confidence: 99%
“…15±17 Other minor mutations, especially the missense mutation S65C, have more recently been identified, and are likely to be associated with mild forms of GH. 20,21 The possible role of HFE mutations in PCT has already prompted some studies that consistently concluded that HFE mutations were significantly higher in patients with PCT than in controls, and that genetic abnormalities of iron metabolism pathways might play a significant part in the physiopathology of the disease. 22±32 We present here a prospective study which further supports this hypothesis and confirms the relative importance of homozygous H63D mutations in patients from southern France.…”
mentioning
confidence: 99%
“…The H63D mutation is two or three times more frequent than C282Y mutation and the prevalence of heterozygous and homozygous for H63D mutation varies between 15 and 40% and 2.5 and 3.6%, respectively, and the frequency of C282Y/H63D genotype is approximately 2% (15,16). Regarding the S65C mutation, the frequency in Caucasians varies between 1% and 4% (9,10,18,19).…”
Section: Discussionmentioning
confidence: 98%
“…Cardoso Nielsen et al, 1998Datz et al, 1997UK consortium, 1997Willis et al, 1997Ryan et al, 1998Mura et al, 1999Moirand et al, 1999 Country HH patients had discordant HFE genotypes in four sibships. A non-expressing HH parent is a likely explanation for the discrepancy observed in two sibships.…”
Section: Referencesmentioning
confidence: 99%